Iowa Birdline update, October 23, 1989 - Fuller, James L.et al; Iowa Ornithologists' Unionet al (1989)
Notes for the Iowa Birdline update for October 23, 1989. Highlights include a Pacific Loon, Horned Grebes and Surf, White-winged and Black Scoters. Epson - sheet feed/flatbed